Inhibition of mitochondrial fission by Drp-1 blockade by short-term leptin and Mdivi-1 treatment improves white adipose tissue abnormalities in obesity and diabetes - Finocchietto, Paola Vanesa (2021)
Background: Obesity and type 2 diabetes are chronic diseases characterized by insulin resistance, mitochondrial dysfunction and morphological abnormalities. Objective: We have investigated if dysregulation of mitochondrial dynamics and biogenesis is involved in an animal model of obesity and diabetes. Methods: The effect of short-term leptin and mdivi-1 – a selective inhibitor of Drp-1 fission-protein – treatment on mitochondrial dynamics and biogenesis was evaluated in epididymal white adipose tissue (WAT) from male ob/ob mice. Results: An increase in Drp-1 protein levels and a decrease in Mfn2 and OPA-1 protein expression were observed with enhanced and sustained mitochondrial fragmentation in ob/ob mice compared to wt C57BL/6 animals (p < 0.05). The content of mitochondrial DNA and PGC-1α mRNA expression –both parameters of mitochondrial biogenesis– were reduced in ob/ob mice (p < 0.05). Treatment with leptin and mdivi-1 signiﬁcantly increased mitochondrial biogenesis, improved fusion-to-ﬁssion balance and attenuated mitochondrial dysfunction, thus inducing white-to-beige adipocyte transdifferentiation. Measurements of glucose and lipid oxidation in adipocytes revealed that both leptin and mdivi-1 increase substrates oxidation while in vivo determination of blood glucose concentration showed decreased levels by 50% in ob/ob mice, almost to the wt level. Conclusions: Pharmacological targeting of Drp-1 fission protein may be a potential novel therapeutic tool for obesity and type 2 diabetes.